Understanding of genes encoding bioactive compounds from potential medicinal plants in Indonesia as cancer cell inhibitors - ZIDNI MUFLIKHATI; NESTI F. SIANIPAR; MAS RIZKY A. A. SYAMSUNARNO; ANAS ANAS (Society for Indonesian Biodiversity, 2023)
Abstract. Muflikhati Z, Sianipar NF, Syamsunarno MRAA, Anas. 2023. Understanding of genes encoding bioactive compounds from potential medicinal plants in indonesia as cancer cell inhibitors. Biodiversitas 24: 4645-4660. Indonesia has abundant plant diversity and enormous potential to be developed as a source of medicinal plants due to the content of bioactive chemicals in them. Potential medicinal plants from Indonesia, such as Andrographis paniculata (Sambiloto), Curcuma longa (Kunyit), Moringa oleifera (Moringa), Phyllanthus niruri (Meniran), Orthosiphon stamineus (Kumis kucing), Typhonium flagelliforme (Keladi tikus), and Zingiber officinale (Jahe), contain bioactive compounds with mechanisms that act as anticancer. Bioactive compounds with anticancer mechanisms in plants can be controlled by specific genes. Therefore, it is important to elaborate on bioactive compounds and the genes involved. This article aims to discuss the genes encoding bioactive compounds in Indonesian medicinal plants and the mechanisms that can inhibit cancer cell growth. Several genes encode anticancer compounds, such as lectin-coding genes, the stigmasterol-coding CYP710A gene, the tocopherol-coding ?-TMT gene, the fatty acid-coding FAD gene, the doxorubicin-coding DXR gene, and the chalcone synthase-coding CHS gene. These genes have mechanisms to increase the expression of several apoptosis-promoting proteins, including BCL-2 family members, in several cancer cell models. This article also describes the potential utilization and creation of molecular markers linked to genes encoding anticancer chemicals and can be used as a reference for research on medicinal plants that is still limited. Knowledge of genes encoding anticancer compounds in plants can support future research in the development of cancer drugs.